2013
DOI: 10.1002/app.39495
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a tung oil–rosin adduct via the diels–alder reaction: Its reaction mechanism and properties in an ultraviolet‐curable adhesive

Abstract: A Diels-Alder adduct of rosin with tung oil was effectively prepared for use as a filler and adhesion promoter in UVcurable adhesives. The characteristics of the adduct were analyzed by Fourier transform infrared (FTIR) spectroscopy and ultravioletvisible (UV-vis) absorption spectra. The reaction mechanism was studied with gel permeation chromatography, thermogravimetric analysis, 1 H-NMR, and the density functional theoretical method. The FTIR and 1 H-NMR results showed that the Diels-Alder addition occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Plant oils have the features of environmentally benign, abundance, biodegradability, and triglyceride structures; thus, they have been used as an ideal substitute to prepare bio-based prepolymers for UV-curable coatings [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Plant-oil-based epoxy acrylate (EA) is one of the common UV-curable prepolymers, which is usually prepared through the ring-opening reaction of epoxidized plant oils with acrylic acid (AA) or its derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Plant oils have the features of environmentally benign, abundance, biodegradability, and triglyceride structures; thus, they have been used as an ideal substitute to prepare bio-based prepolymers for UV-curable coatings [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Plant-oil-based epoxy acrylate (EA) is one of the common UV-curable prepolymers, which is usually prepared through the ring-opening reaction of epoxidized plant oils with acrylic acid (AA) or its derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Resin synthesis was performed by acrylation of TO via Diels-Alder (DA) reaction and the successful reaction was confirmed by ATR-FTIR. In Figure 1a, the FTIR spectrum of TO showed a shoulder peak at 3012 cm −1 (Figure 1b) and a strong signal at 996 cm −1 corresponding to the trans-trans conjugated double bonds, and a weak peak at 964 cm −1 arising from the cis double bonds (Figure 1a) [39]. The sharp signal at 1742 cm −1 was attributed to ester-carbonyl stretching.…”
Section: Resultsmentioning
confidence: 97%
“…Some studies have shown that the unique ring structure of rosin can reduce the stress generated in the curing process of buffer film and smoothens the surface of the buffer film after curing. Wu et al [80] used the above-mentioned characteristics to modify TO with rosin. After hydroquinone was added into the container, D-A reaction occurred between TO and rosin in different proportions to obtain a TO Figure 5: Synthesis and theoretical structure of HG-MAT and PG-MAT [76] rosin D-A product, as shown in Fig.…”
Section: Modification Of To By Other Dienophile D-a Addition Reactionsmentioning
confidence: 99%